Economic indicators and electoral volatility: economic effects on electoral volatility in Western Europe, 1950–2013. Issue 6 (October 2017) - Dassonneville, Ruth; Hooghe, Marc
Abstract Economic voting theory assumes that on an individual level voters react to economic indicators to hold incumbents responsible for the performance of the economy. On an aggregate level, this would imply that there is an association between economic indicators and levels of volatility since voters have to switch parties if they want to punish or reward political actors. Based on a time-series cross-section analysis of the Pedersen Index for Western European countries in the period 1950–2013, we do indeed observe an association between economic indicators and levels of volatility. This effect furthermore grows stronger over time, and it is assumed that this is rendered possible by processes of partisan dealignment. The analysis suggests that European electorates are significantly more likely to shift parties in response to economic downturn now than they were a few decades ago.